Aktivitas Harian Monyet Hitam Sulawesi (Macaca nigra) di Cagar Alam Tangkoko-Batuangus, Sulawesi Utara - Saroyo Saroyo; Sri Supraptini Mansjoer; Rudy C Tarumingkeng; Dedy Duryadi Solihin; Kunio Watanabe (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
This study was conducted on Rambo II Group at Tangkoko-Batuangus Natural Preservation, North Sulawesi, from January to February 2004. Data were collected using scan sampling with two minute interval. The results showed that the daily activities of the monkey group consisted of feeding and foraging (34.55%), moving (18.70%), resting (28.65%), and social behaviour (18.10%). It could be concluded that there was no difference between the daily activities of Rambo II Group and those of Rambo Group, the original group before being fragmented into Rambo I and Rambo II Groups.